Macrocyclic and polymeric lanthanide chelates: from physico-chemical studies to biomedical applications - Duarte, M. G. (2002)
The improvement of commonly used Gd3+-based MRI contrast agents requires the design of new chelates with optimised in vivo efficacy, pharmacokinetic properties and specificity. The molecular parameters determining the nuclear relaxivity of the cationic chelate [Gd(DO2A)]+, as well as of some copolymers of [Gd(DTPA)]2- with diamines, were obtained using spectroscopic techniques. In both cases, the resulting too slow inner-sphere water exchange rate limits the relaxivity increase expected, respectively, from an increased water coordination number, and some degree of rotational restriction, although in the latter case, the relaxivity shows a maximum in the 30 MHz proton frequency region. The use of the polymeric compounds as MR angiography agents is limited by their fast uptake from the blood pool of Wistar rats. The use of scintigraphic diagnostic agents critically depends on their targeting properties. 111In3+ and 153Sm3+ chelates of DTPA derivatives, containing albumin binding or hepato-specific synthons, show different organ specificity, albumin binding properties and excretion pathways and kinetics, as shown by biodistribution and gamma imaging studies of Wistar rats. The 111In3+, 153Sm3+, Gd3+ and Tm3+ chelates of the tetraaza-phosphonate macrocycle DOTP8- also show high bone uptake specificity.